Inter-professional Collaboration in Managing Chronic Diseases: Nurses, Public Health Experts, and Mental Health Specialists Systematic Review - Wael Mohammed HussainTalea,; Yahya Mohammed Hussain Zaybi,; Ibrahim Hassan Ibrahim Albanawi,; Ali Mohammed Ali Harmali,; Mohsen Ali Ahmed Maashi,; Hafiz Yahya Ali Khubrani, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Numerous studies have demonstrated the advantages of teamwork, including as improved care coordination and continuity, positive behavioral changes in patients, and an increase in patient symptoms and satisfaction through better needs-based responses. But research also indicates that putting it into practice can be difficult. Professional collaboration may be jeopardized in practice if practitioners are not persuaded of its advantages for patients, or if primary care physicians believe it would result in a loss of ongoing, comprehensive patient care, a loss of their professional identity, or a loss of the qualities that make their jobs unique. This present study also tried to add value to the above said line of research and hope to pave the path for future researchers. Study is based on secondary data and takes into account KSA as the ground as a geographical location.